ANALISIS SOSIOLOGIS TERHADAP TOKOH UTAMA DALAM NOVEL OUT KARYA NATSUO KIRINO - asking - (Jurnal Puitika, 2013)
Literature is a medium to publish thought, idea and advice from an author to a reader. The thought, idea or advice such as moral message, problem solution, etc. OUT novel is a popular novel written by Natsuo Kirino. It expresses the main characters faced in thier life such as family problems, disharmony family problems, consumerism lifestyle problems and fatigue life problems. The uniqe of OUT is that all of the main characters in this novel are woman, they are Masako Katori, Yayoi Yamamoto, Yoshie Azuma and Kuniko Jonouchi. These main characters want to solve their problems in order to achieve what they  wanted. The purpose of this research is to know about problem which faced by the main characters and the freedom that they want in their life. After analysing the characters of OUT based on sociological approach, the research shows that the social problem the characters faced are different each other, the novel pictures the women’s life in their family, the characters can solve their problems by their own way. Key words : woman , social problems, family